A Study of South Sorsogon Verbs - Escalante, Antonio H. (The Archive; Vol 11 (1996): Publication Eleven: Three Studies on Philippine Morphology, 2025)
The South Sorsogon language is spoken in a contiguous area in the South-Southeastern half of the province of Sorsogon. It is also spoken in the leeward side of Beri Island, geographically and politically of Northern Samar, where the eastern linguistic boundary is located. It is one of four known dialects in the province, two of which, including South Sorsogon, have Bisayan linguistic affinities, and two being of Bikol. It is spoken in 7 of the province’s 16 towns, roughly the political 1st congressional district. Its speakers comprise about 60% of the province’s population, and it has three of the province’s four most important towns in Bulan, Gubat and Irosin. Oddly, although the speakers of this language within the dialect area acknowledge the identity of the inter-municipality speech, which differs only in a few lexical items and intonation from the ‘flat intonation’ of the ‘inner belt’ of Bulan-Irosin-Gubat to the ‘wide swings’ of the outermost towns of Bulusan and Sta. Magdalena at the southernmost tip of the province and Luzon Island), there is no name for the language, a testimony to the length of time1 of the dialect differentiation and the ‘barangay mentality’, the propensity to think only in terms of the barangay, or the municipality of late. The people of Gubat would say their speech is Ginobatnon, the people of Bulusan- Bulusanon, and so forth. Often, it is the misnomer ‘Bikol’ that is used to name the language, possibly because the linguistic area is of the Bikol region geographically and politically. This thesis aims to describe and analyze the verbal structure of this language. The category ‘verb’ has also its internal co-occurent structures; i.e., it inflects, by affixation, for the various grammatical distinctions such as tense/aspect, number, voice, mood and ‘case function’. The isolation and description of these various distinctive forms or morphemes or formatives that occur or co-occur with the root or stem to form the category ‘verb’ is the aim of this thesis.